An approach to offline handwritten Devanagari word segmentation. (30th October 2012) - Murthy, O.V. Ramana; Hanmandlu, M.
Hindi is very popular language after Mandarin and English. Its script is Devanagari. Although major work is reported on OCR techniques for machine printed Devanagari script, very few works are beginning to report on offline handwritten Devanagari OCR. Particularly, very few works have been reported so far on segmentation of Devanagari words. This paper paves a step in that direction and open avenues for researchers in that field. A novel segmentation approach is proposed for segmentation of offline handwritten Devanagari words using techniques of Hough transform and connected components. The difficulties for segmentation in Devanagari script and systematic steps to accommodate those difficulties as much as possible have been presented with elaborate results.